Porphyrin protonation studied by magnetic circular dichroism - Štěpánek, Petr; Andrushchenko, Valery; Ruud, Kenneth; Bouř, Petr (The journal of physical chemistry. A, 2012)
Magnetic circular dichroism (MCD) spectroscopy provides valuable information about electronic excited states in molecules. The interpretation of spectra is however difficult, often requiring additional theoretical calculations to rationalize the observed signal. Recent developments in time-dependent density functional theory (TDDFT) bring hope that the applicability of MCD spectroscopy for chemical problems may be significantly extended. In this study, two modern analytical TDDFT implementations are compared and used to understand experimental MCD spectra of a model porphyrin system upon protonation. Changes in porphyrin geometry and electronic structure are related to MCD intensities by comparing the spectra of 5,10,15,20-tetraphenyl-21H,23H-porphyrintetrasulfonic acid (TPPS) measured at different pH values with the TDDFT calculations. Although the theoretical results slightly depended on the chosen exchange-correlation functional, the computations provided MCD curves that could well rationalize the experimental data. The protonation of the porphyrin core causes marked changes in the MCD spectrum, whereas the role of the substituents is limited. Also, different conformations of the porphyrin substituents cause relatively minor changes of the MCD pattern, mostly in the Soret region, where the porphine and phenyl electronic transitions start to mix. The solvent environment simulated by the dielectric model caused a shift (~20 nm) of the absorption bands but only minor variations in the absorption and MCD spectral shapes. The study thus demonstrates that the recently available first-principles interpretations of MCD spectra significantly enhance the applicability of the technique for molecular structural studies.